A Systematic Review on Micronutrients in Memory: Feeding the Brain - Bhoir, Anjali; Patil, Rupali; Boraste, Sahebrao; Pingale, Prashant; Amrutkar, Sunil (The Indian Journal of Nutrition and Dietetics, 2022)
Treatment with micronutrients resulted in substantial gains on measures of verbal learning and memory. Identifying and preventing sub-clinical deficiencies may be necessary to avoid the negative effects of undernutrition.The molecular mechanisms of micronutrients must be understood in food’s impact on memory can assist us to find out how to better control nutrition to improve neuronal tolerance to encourage mental health. Food’s ability to prevent and combat disease is becoming more universally understood. Over the last five years, the research has shown intriguing evidence for the impact of dietary variables on complex biochemical processes and pathways that promote mental function. Our brain is similar to a muscle in that the more we utilize it, the stronger it becomes. At every age-as student, professionals, and the elderly-we require our brain to work optimally, as well as retrieve information that we have acquired or experienced. Memory consolidation is aided by “healthy habits” such as a proper diet and adequate sleep. It also contributes to the brain’s optimal functioning. However, the most significant method is through nutrition and nutrients, which have no side effects or contraindications. A diet high in omega 3 fatty acids, for example, is being praised for its capacity to improve cognitive processes in both humans and animals. This review aimed to emphasize on micronutrients in memory.